COCONUT TAPPING IN THE PHILIPPINES ENIGMAS AND OBSERVATIONS - Rebecco M. Santiago; Ma Solita J. Virtudazo (International Coconut Community Journal, 1996)
Individual interviews were conducted to 24 purposively selected coconut tappers from Leyte, Samar and Cebu, Philippines to determine their tapping practices and observations and knowledge on certain phenomena exhibited by the tapped palm, as well as, the problems which confront them. Specifically, inquiries were focused on tree selection, spadix/inflorescence age appropriate for tapping, spadix preparation and stimulation, spadix care and maintenance, climatic considerations and relations, and temporary cessation of inflorescence production. Data revealed certain enigmatic phenomena and some inconsistencies to long‑held physiological facts. Moreover, respondents' observations strongly point out the toddy yield's extreme sensitivity to climatic and weather change which could be best validated by further coconut physiology research.